2017
DOI: 10.1508/cytologia.82.413
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Origin of Amphidiploids in the Complex Species of <i>Scilla scilloides</i>, Asparagaceae

Abstract: In the complex species of Scilla scilloides involving A and B genomes, an amphi diploid having AABB genome composition is a major one of the cytotypes and distributes throughout a growing area of the species. An origin of amphi diploids and whether amphi diploids generated in monophyly or polyphyly are unsolved. In three hybrids with defied combination of genomes a maternal inheritance of chloroplast genome was confirmed in this species. An analysis of matK sequence of chloroplast genome demonstrated that a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…The results of the extensive chromosomal survey were largely in agreement with previous reports from Chinese, Japanese, and Korean populations [22,23,62]. Genome sizes reported here, however, deviated from those reported by Shibata et al [20]. The discrepancies (i.e., quite consistent and approximately 2 pg/1C deviation) are likely to represent methodological problems, as the previous genome size values have been obtained via ow cytometry with less accurate DAPI staining of the DNA and using Allium stulosum as an internal standard [63].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the extensive chromosomal survey were largely in agreement with previous reports from Chinese, Japanese, and Korean populations [22,23,62]. Genome sizes reported here, however, deviated from those reported by Shibata et al [20]. The discrepancies (i.e., quite consistent and approximately 2 pg/1C deviation) are likely to represent methodological problems, as the previous genome size values have been obtained via ow cytometry with less accurate DAPI staining of the DNA and using Allium stulosum as an internal standard [63].…”
Section: Discussionsupporting
confidence: 92%
“…Dysploidy as well as auto-and allopolyploidy within species complexes have been reported in many species in family Hyacinthaceae (also treated as Asparagaceae; [13,[18][19][20][21]). The genus Barnardia Lindl.…”
Section: Introductionmentioning
confidence: 99%
“…Barnardia numidica is widespread in the Balearic Islands and North-West Africa (Algeria, Tunisia, and Libya) and is known only as diploid with 2 n = 18 ( x = 9; [ 27 ]). In contrast, the B. japonica complex is found in Eastern Asia and exhibits a spectacular array of chromosomal variation with two different base chromosome numbers ( x = 8 and 9), an extensive range of polyploids (3 x , 4 x , 5 x and 6 x ), various types of chromosomal polymorphisms including the presence of B-chromosomes [ 28 , 29 ], as well as genome size variation [ 22 ]. Molecular phylogenetic studies of plastid and nuclear DNA sequence data have revealed that the B. japonica complex is the most basal clade in the family of Hyacinthaceae [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, no morphological diagnostic characters have so far been found to allow for identification of the two diploid cytotypes and their hybrid/polyploid descendants in the B. japonica complex [ 25 ]. Thus, the current species concept in the B. japonica complex is mostly based on classical karyotaxonomic studies with two diploid cytotypes differing in base chromosome number and a myriad of resulting polyploid cytotypes [ 22 , 24 26 , 28 , 35 , 59 ], while the underlying patterns of genetic and micromorphological differentiation are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Flowering, which is one of the most sophisticated survival mechanisms that evolved in plants, involves meiosis, which can increase the genetic diversity of progeny through recombination due to the pairing of homologous chromosomes (Gupta et al 2017a, b, 2018a, b, Jeelani et al 2017, Kumar et al 2017, Liébana et al 2017, Rani et al 2017, Saggoo and Kaur 2017, Singhal and Kumari 2017, b, Dhaliwal et al 2018a, b, Farooq and Saggoo 2018, b, Kumari and Singhal 2018. Genetic diversity has resulted in the development of various phenotypes depending on environmental factors, and is one of the driving forces responsible for increases in the geographical distribution of certain plant species (Bordbar et al 2017, Shaker et al 2017, Shibata et al 2017, Muakrong et al 2018, Özer et al 2018, Senavongse et al 2018, Tapia-Pastrana et al 2018.…”
mentioning
confidence: 99%